SHARIA ACCOUNTING LITERATION AND FRAUDS PREVENTIVE ON FINANCIAL REPORTING IN SHARIA FINANCIAL INSTITUTIONS - Asri Noer Rahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2021)
The purpose of this study to know literacy and Islamic accounting applications against fraud prevention in financial reporting in Islamic Financial Institutions and to apply Islamic values to accountants or auditors in order to prevent fraud in financial reports that often occur. Fraud detection is essential to increasing the value of auditing, but there are many problems that can hinder the implementation of proper detection. Based on a review of various studies that have been carried out, the Sharia accounting application is good, which implements a profit sharing system (avoids usury), there is also a separation of financial reporting for each contract, separation of reporting zakat, infaq and shadaqah reporting. In detecting fraud prevention, there are four factors that can prevent fraud in financial reporting identified through this study. First, the auditing standards are insufficient to support proper detection. Second, the characteristics of the occurrence of fraud make it difficult to detect fraud. Third, there is a lack of knowledge of Islamic values in the Sharia accounting application so that fraud does not occur, and the fourth is that there must be awareness that financial statement analysis is not only responsibility for the company, interested parties and decision-holders, but also accountability. who will be accountable in the hereafter, if fraud occurs, then they must be prepared to bear their sins in the hereafter.